2017
DOI: 10.1002/jpln.201700144
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrients and metals released from soils by solutions of naturally occurring phenols

Abstract: Phenolic compounds produced by plants enter the soil by leaching and litter decomposition. The goal of this work is to determine the effect of phenolic compounds on solubility of plant macronutrients and metals in agroforestry systems. Soils from forest and pasture systems were repeatedly extracted with water (control) or phenolic solutions and then compared to a Mehlich 3 reference. The phenolics were aqueous solutions of tannic acid or β–1,2,3,4,6‐penta‐O‐galloyl‐D‐glucose (PGG) (hydrolyzable tannins), procy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…This pattern was independent from the growing condition, albeit showing different variations according to the starvations (Figure 5). In particular, phenols and coumaric acids showed a general increase in all the conditions; indeed, the exudation of phenols has already been shown to be involved in the response to Fe starvation, possibly for the mobilization of sparingly soluble Fe sources [52][53][54][55]. Moreover, phenolics can increase the solubility and the uptake of metals such as Fe by chelation or reduction [52,[54][55][56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern was independent from the growing condition, albeit showing different variations according to the starvations (Figure 5). In particular, phenols and coumaric acids showed a general increase in all the conditions; indeed, the exudation of phenols has already been shown to be involved in the response to Fe starvation, possibly for the mobilization of sparingly soluble Fe sources [52][53][54][55]. Moreover, phenolics can increase the solubility and the uptake of metals such as Fe by chelation or reduction [52,[54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, phenols and coumaric acids showed a general increase in all the conditions; indeed, the exudation of phenols has already been shown to be involved in the response to Fe starvation, possibly for the mobilization of sparingly soluble Fe sources [52][53][54][55]. Moreover, phenolics can increase the solubility and the uptake of metals such as Fe by chelation or reduction [52,[54][55][56]. Similar results were found by other authors who showed that the Arabidopsis phenylpropanoid pathway is stimulated in roots by Fe-deficiency [54,57].…”
Section: Discussionmentioning
confidence: 99%
“…Because the original pH in the TA solution was acidic (pH 4.0), it favored the release of alkaline cations from the calcareous soil, resulting in a sudden increase in the pH of the leachate. Due to the fact of its acidic nature, TA can efficiently extract Ca and Mg from soil [ 34 ]. Between the 10th and 30th hour of soil flushing, the pH in the leachate stabilized ( Figure 3 a).…”
Section: Resultsmentioning
confidence: 99%
“…After the soil was saturated with TA, its concentration in the leachate stabilized and was close to the concentration in the original solution. The tendency of TA to sorb to soil can be a critical determinant of metal mobilization, as this tendency limits its ability to form soluble extractable complexes with metals [ 34 ]. A decrease in flushing solution concentration is typical during soil flushing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation